Will there be a concentration of alikes? The impact of labor market structure on industry mix in the presence of product market shocks - Konrad O. Stahl; Uwe Walz (Hamburg Institute of International Economics (HWWA), 2001)
We analyze determinants of regional industry mix and focus especially on the influence of labor market characteristics. By combining a labor market pooling argument with an argument involving the cost of switching a worker from one firm to another, we show that in the presence of product market shocks there exists an interesting trade-off for the concentration of firms of the same industry in one region. Firms belonging to different industries are hedged against industry-specific shocks if they settle in the same region, but face higher switching costs (retraining costs for workers moving from one firm to another). In addition, with a given supply of labor there is an additional rationing effect affecting the location decisions of firms. Against the background of these trade-offs we analyze the resulting location decisions of firms in a two-regions-two-industry-four-firm framework. We analyze the impact of different parameters on the location choice of firms.
Keywords: L1; J4; R3; 330; local labor market; product market shocks; industry structure; imperfect competition; Regionalökonomik; Regionale Wirtschaftsstruktur; Regionaler Arbeitsmarkt; Arbeitsmarktsegmentierung; Regionale Konzentration; Schock; Betriebliche Standortwahl; Umschulung; Anpassungskosten; Theorie